A Case of Impending Cardiac Tamponade Caused by Effusive Constrictive Pericarditis - Sanchez-Alvarez, Catalina; Werlang, Monia; Oluleye, Oludamilola; Yamani, Mohamad H (Archives of Clinical and Medical Case Reports, 2018)
Pericarditis is the most common pericardial disease worldwide, and can be recurrent in one third of the patients with viral and idiopathic pericarditis [1]. The diagnosis of pericarditis should be based on clinical criteria, history, clinical findings, electrocardiographic (ECG) changes and evidence of a pericardial effusion [2]. Elevation of the inflammatory markers and evidence of pericardial inflammation by an imaging technique such as contrast enhancement on the pericardium-CT scan or pericardial edema and pericardial late gadolinium enhancement on cardiac magnetic resonance imaging (MRI) are additional supportive criteria in the diagnosis [1].